Evaluation of Poison Baits and Bacillus thuringiensis var. kurstaki Against Spodoptera litura in Tomato - Sharma, Anurag; Raina, Rajeev; Kapoor, Renu; Thakur, Kehar Singh (International Journal of Economic Plants, 2020)
Spodoptera is a polyphagous and most destructive pest of most of crops including tomato. The bioefficacy of poison baits with Methomyl and Bt formulations was observed along with male flight activity of the tobacco caterpillar in tomato open field crops. The study was conducted in three villages of Chamba district viz. Sahu, Bhanauta and Kiri during 2019-2020. Tomato is one of the important cash crops in many parts of district Chamba and a source of livelihood of small and marginal farmers of the district. It is cultivated in an area of about 294 hectares with the annual production of 11,410 MT. Tobacco caterpillar, Spodoptera litura (Fab.) (Lepidoptera: Noctuidae) is a polyphagous and sporadic pest and is nocturnal pest in nature. The bioefficacy results revealed that the % mortality of baits with insecticide (ranging from 10.24% to 83.24%), baits with BT formulation (15.64% to 81.06%) and spray of Bt formulations (14.10% to 85.60%) in fields did not differ significantly at the respective days. It was also observed that the peak activity was observed in the months of June and July (maximum 20 adult trapped trap-1) and hence capturing the male adults this time resulted in fewer larval population of the insect-pest. Thus, these practices could be included in IPM of the insect pest and confirmed the importance of eco-friendly methods against lepidopteron species.